Strategies for Strengthening Early Childhood Social and Emotional Intelligence in the Digital Era at Pembina Tanjung Batu Kindergarten - Sakiratul Niam; Iqlima, Iqlima; Novita Loka (STIT Attaqwa, 2025)
Social-emotional intelligence development is a fundamental aspect of early childhood growth that influences their ability to interact, manage emotions, and adapt to social environments. During the golden age period, particularly in the 4-6 years age range, children experience a critical phase in forming social-emotional skills that become the foundation for personality development in the future. The digital era brings new challenges to children's social-emotional development, particularly regarding the impact of excessive screen time that can hinder social interaction and emotional regulation abilities. This study aims to analyze strategies for strengthening social-emotional intelligence of early childhood in the digital era at TK Pembina Tanjung Batu. This research employs a descriptive qualitative approach with research subjects consisting of 16 children in group B (aged 5-6 years), 3 classroom teachers, and the school principal. Data collection techniques include participatory observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman model through data reduction, data display, and conclusion drawing stages. Research results show that 82.1% of children achieve social-emotional intelligence development in the categories of very well developed and developed as expected. The strategies implemented include collaborative project-based learning, use of educational digital media such as cartoons about patience and self-control, strengthening direct social interaction activities, and parental involvement through digital literacy parenting programs. The aspects of social interaction ability, cooperation, and verbal communication show the highest achievement (87.5%), while emotional regulation and sharing ability require special attention (75%). This research recommends developing a digital era-responsive curriculum, strengthening parenting education programs, and optimal balance between technology-based learning and direct social interaction to optimize social-emotional intelligence development in early childhood.